Advancing agricultural development through horticultural extension services - Wiraguna, Edi; Ardiansyah, Agi Juan; Rochmah, Hidayati Fatchur; Meliala, Merry Gloria; Azhar, Aidil; Dahliani, Lili; Purnamawati, Iis; Russianzi, Wanda; Muliasari, Ade Astri; Dardanella, Derry (Universitas Syiah Kuala, 2024)
Horticultural extension services in Bogor are instrumental in promoting agricultural development by enhancing the productivity and sustainability of local horticultural practices. This study emphasizes the empowerment of women farmer groups, known as Kelompok Wanita Tani (KWT), to improve horticultural production through targeted initiatives such as providing essential production facilities and enhancing the skills of farmers and extension officers. Data collection was conducted from July to September 2024, using questionnaires and surveys to assess the knowledge of KWT members before and after extension activities. The results indicated a significant increase in knowledge related to horticultural crop cultivation, with pre-test scores rising from 69% to 87% post-training, demonstrating a 17% improvement (P0.01). This improvement in knowledge and practices is a promising sign for the future of horticultural development. Correlation analysis revealed interesting relationships among agricultural knowledge, educational background, age, and agricultural experience. This research highlights the crucial role of extension services in disseminating knowledge and best practices, ultimately improving the livelihoods of farmers in Bogor and contributing to the local economy.